PENGARUH PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 DENGAN TINGKAT KECEMASAN MAHASISWA/I UNIVERSITAS YATSI MADANI - Safinah Fatimah; Sari Lestari; Ayu Pratiwi; Febi Ratnasari (Nusantara Hasana Journal, 2023)
At the beginning of 2020 the world was shocked by the presence of a new virus originating from Wuhan, China. A virus called Coronavirus Diseases which is abbreviated as COVID-19. The emergence of the COVID-19 Virus that emerged in early December 2019, became one of the triggers for the level of concern that could cause anxiety and is still a hot topic of conversation among the public, especially students. This study aims to determine the effect of online learning on the level of anxiety experienced by Yatsi Madani University students during the Covid-19 pandemic. This type of research is causal comparative with cross sectional approach. The sample in this study used purposive sampling with the slovin formula, it was found that there were 138 respondents from level 3 semester 6 students of Yatsi Madani University who had met the specified inclusion criteria. The results of the chi square test obtained a P-value of 0.000 <0.05, indicating that there is an influence between online learning and student anxiety levels. There is a significant effect on the level of severe anxiety experienced by students with online learning which is deemed ineffective during the Covid-19 pandemic on level 3 students at Yatsi Madani University.